2021
DOI: 10.1007/s11769-021-1173-0
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Hidden Markov Model to Analyze Urban Mobility Patterns: An Interdisciplinary Approach

Abstract: With the emergence of the Internet of Things (IoT), there has been a proliferation of urban studies using big data. Yet, another type of urban research innovations that involve interdisciplinary thinking and methods remains underdeveloped. This paper represents an attempt to adopt a Hidden Markov Model (HMM) toolbox developed in Computer Science for the analysis of eye movement patterns in Psychology to answer urban mobility questions in Geography. The main idea is that both people's eye movements and travel b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Especially, we see that time series analysis methods are becoming more and more practical, and then some practical time series analysis software has appeared. Gradually, time series analysis methods and software have become impossible to predict and analyze those seemingly unrelated data [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, we see that time series analysis methods are becoming more and more practical, and then some practical time series analysis software has appeared. Gradually, time series analysis methods and software have become impossible to predict and analyze those seemingly unrelated data [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…We have also used EMHMM to develop benchmarks for evaluating XAI methods (Yang, Folke, & Shafto, 2022). EMHMM has also been used in other fields including Behavioral Dentistry and Urban Mobility research (Loo, Zhang, Hsiao, Chan, & Lan, 2021; Zhang, Loo, Lan, Chan, & Hsiao, 2023). For example, in Behavioral Dentistry, by applying EMHMM to analyze children's eye movement behavior when viewing images with dental caries/injuries, we found that while poor dental aesthetics due to untreated caries or traumatic dental injuries are suggested to have adverse emotional and social impacts in adults, most preschool children did not show any attention bias toward or away from caries/injuries.…”
Section: Attention Strategymentioning
confidence: 99%
“…Also, most preschool children showed attention bias toward a midline diastema, whereas their educators averted their eyes, suggesting different interpretations between children and adults (Cho et al., 2022c). In Urban Mobility, through applying EMHMM to model and cluster travel patterns of working adults in Hong Kong, we discovered balanced versus work‐oriented lifestyle groups, with those living in the urban core demonstrating a more work‐oriented lifestyle (Loo et al., 2021; see also Zhang et al., 2023). We have developed an EMHMM Matlab toolbox, publicly available at http://visal.cs.cityu.edu.hk/research/emhmm/.…”
Section: Attention Strategymentioning
confidence: 99%